Metamaterial sensor based on reflected mirror rectangular split ring resonator for the application of microwave sensing. (July 2022) - Rashedul Islam, Md.; Tariqul Islam, Mohammad; Soliman, Mohamed S.; Bais, Badariah; Jit Singh, Mandeep; Alsaif, Haitham; Shabiul Islam, Md.
Highlights: A new metamaterial sensor is created to identify various materials as well as their thickness. Various parametric analysis has been done to optimize the design and size of the structure. The equivalent circuit of the structure is designed using ADS and its performance is verified with CST. The proposed sensor's originality is its high sensitivity, high-quality factor, unique compact structure, and ease of use. The recommended structure is highly sensitive and can be used in various industrial applications. Abstract: In this research paper, a new reflected mirror rectangular split-ring resonator-shaped metamaterial sensor is proposed for the detection of materials and thickness of the materials. The metamaterial structure is designed in the same dimension as the opening of the X-band waveguide as if a total guided electromagnetic wave penetrates the structure, and its size is 22.86 × 10.16 mm 2 . Computer simulation technology (CST) microwave studio is used to design the metamaterial structure and the obtained reflection coefficient is validated with the advanced design system (ADS) results. Various parametric analysis has been done to optimize the design and size of the structure. Three materials FR-4, Rogers RO4350B, Rogers, and RT5880 have been attached to the metamaterial sensor and have shown the overall results both experimentally and theoretically. The resonance frequency shifted 120 MHz between FR-4 and Rogers RO4350B, and 250 MHz shifted between FR-4 and Rogers RT5880. Three different thicknesses of the FR-4 have been used to see the response of the metamaterial sensor. The resonance frequency shifted 80 MHz between 1.6 and 1.3 mm thickness of the FR-4, and 110 MHz shifted between 1.6 and 1 mm thickness of the FR-4. The simulated and measured outcomes are quite similar. The sensitivity of the structure is 1.29 and the quality factor (Q-factor) is 435, the figure of merit (FOM) is also analyzed, and its value is 561.15. Since the proposed sensor has high sensitivity, high Q-factor, and shows better performance, hence it can be used in industry to detect the various materials and thickness of the materials.